Application of biotic ligand and toxicokinetic–toxicodynamic modeling to predict the accumulation and toxicity of metal mixtures to zebrafish larvae. (June 2016) - Gao, Yongfei; Feng, Jianfeng; Han, Feng; Zhu, Lin
Abstract: Predicting the accumulation and toxicity of mixtures of metals to aquatic organisms is a key challenge in ecotoxicological studies. In this study, the accumulation and toxicity of mixed essential (Cu) and nonessential (Cd and Pb) metals in zebrafish larvae exposed to a binary mixture of these elements at environmentally relevant concentrations were predicted using a refined toxicokinetic (TK)–toxicodynamic (TD) model aided with biotic ligand model (BLM) and toxic equivalent factor (TEF) approach. Competitive inhibition and non-competitive interaction/inhibition were observed in bio-uptake. Both Pb and Cd behaved as competitive inhibitors of Cu uptake at high Cu concentrations (>0.1 μM). By contrast, Cu uptake was independent of Cd or Pb when the Cu concentrations were below 10 −7 M. Furthermore, low concentrations of Cu had an adiaphorous effect on Cd or Pb uptake. Cd uptake was inhibited by Pb, and the Pb uptake rates consistently decreased in the presence of Cd. The accumulation processes of Cd–Pb, Cu–Cd, and Cu–Pb were accurately predicted by the BLM-aided TK models. The traditional TD model could successfully predict the toxicity of Cd–Pb mixtures, but not those of Cu–Cd or Cu–Pb mixtures. The revised TD model, which considered the possible different killing rates ( K k ) above or below the threshold, offered better prediction for the toxicity of Cu–Cd or Cu–Pb mixtures. The overall findings may be of key significance in understanding and predicting metal uptake, accumulation, and toxicity in binary or multiple metal exposure scenarios. Graphical abstract: Highlights: A toxicokinetic-toxicodynamic model was used to predict the toxicity of mixed metals. Both Pb and Cd behaved as competitive inhibitors of Cu uptake at high Cu 2+ levels. Low concentrations of Cu 2+ had an adiaphorous effect on Cd or Pb uptake. The toxicodynamic model successfully predicted the toxicity of Cd–Pb mixtures. The revised toxicodynamic model better predicted the toxicity of Cu mixtures. Abstract : Toxicity of mixed metals was predicted using a toxicokinetic–toxicodynamic model.